Load frequency control of wind integrated power systems using intelligent control techniques - Bhardwaj, Nitish (My University, 2018)
The load frequency control (LFC) is an important problem to maintain constant frequency of the electric power systems operation. Most LFCs are primarily equipped with integral controllers. The integral gain is set to a level that the compromises between fast transient recovery and low overshoot in the dynamic response of the overall system. Moreover, these controllers are slow and do not allow to take in to make changes in operating condition and non-linearity in the generator unit. Doubly Fed Induction Generator (DFIG) based wind turbines run at variable speed, resulting in the variable power generation and also possess non-linearity in the systems. Large frequency deviation due to higher wind power penetration. This puts pressure on thermal and fast response generators (Increased requirements on system flexibility). Moreover, it lacks in robustness. Hence, Artificial Neural Networks (ANN) based controllers can relieve these problems. The proposed study of LFC has implemented ANN based NARMA L_2 controllers on two area wind integrated power systems for simulation to study dynamic response of control areas with different loading condition. The simulation results obtained are satisfactory. The results suggest that ANN based NARMA L_2 provides better control to wind integrated non-linear systems.
Keywords: Load frequency control, PI Controller, DFIG, ANN, NARMA-2